End-of-Life: A Religious Studies Perspective - Davies, Douglas J. (Concilium, 2021)
In this article, individual end-of life issues are aligned with those of the earth's survival, both framed by ecological-environmental factors. Notions of personhood set "the individual" against "dividual" or complex identity as we consider how emotions turn ideas into values, identities, and even destinies, as ecological issues grow. Older and newer forms of animism, souls, gift or reciprocity theory, merit-making, and the question of life-sustaining narratives are explored alongside innovative forms of funeral that celebrate life more than they curate sinners.